Kierkegaard : A Very Short Introduction - Gardiner, Patrick (Oxford Oxford University Press, 2002)
Soren Kierkegaard (1813-55), one of the original thinkers of the nineteenth century, wrote on religious, psychological, and literary themes. This book shows how Kierkegaard developed his views in emphatic opposition to prevailing opinions. It provides an introduction by showing how Kiekegaard has influenced contemporary thought.
Include Illustrations, Abbreviations, References and Index.
A Very Short Introduction.
Keywords: PhilosophyKierkegaard, Søren, 1813-1855 -- Philosophy, Danish